Telemicrosurgery Robot Assisted Microsurgery - Liverneaux, Philippe A.; Berner, Stacey H.; Bednar, Michael S.; Parekattil, Sijo J.; Mantovani Ruggiero, Gustavo; Selber, Jesse C.; SpringerLink (Online service) (Paris : Springer Paris : Imprint: Springer, 2013)
The purpose of this book is to define the basis of telemicrosurgery, a new discipline at the border of robotics and microsurgery. After the history of robotics and microsurgery, the robots and their instrumentation will be described. The chapters will explain the training in telemicrosurgery and then propose some experimental paradigms. The first clinical applications for various specialties will be explored. In closing, potential future applications will be discussed.
Preface -- Foreword -- History of microsurgery -- History of telesurgery -- Description of robots -- Instruments -- Set up (portals, insufflation, retractors).-Earthworms -- Vessels -- Nerves -- Free tissue transfert -- Teleendosurgery -- Brachial plexus repair -- Tendon transfert -- Nerve entrapment -- Nerve repair (fascicle) -- Brachial plexus -- Skin flaps -- Muscle flaps -- Head and necks -- Urology -- Supermicrosurgery -- Network.
Keywords: Medicine; Orthopedic surgery; Surgery; Urology; Medicine & Public Health; Surgery; Surgical Orthopedics; Urology/Andrology.